Quark condensates and high density quark matter - Panda, P. K.; Krein, G.; De Carvalho, RSM (World Scientific Publ Co Pte Ltd, 2003)
We consider a Coulomb gauge quark model which includes an explicit construct for a nontrivial vacuum structure in QCD. The dynamics is described by a Hamiltonain that contains a linearly rising confining potential and longitudinal and transverse Coulomb-type interactions. The Coulomb potential gives rise to ultraviolate divergences which are non-perturbatively renormalized by adding appropriate counter terms to the Hamiltonian. The equation of state for u and d quark matter at zero temperature is derived in the Hartree-Fock approximation.